Waste Management Education for Talas Beneng-based Product Production in Talaga Warna Village, Pabuaran District, Serang Regency - Cahyani, Ferina Ardhi; Putri, Nia Ariani (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2023)
Beneng taro a raw material used in the production of taro-based products, is managed by the Women Farmers Group in Tanjung Kulon Village, Pabuaran District, Serang Regency. However, the management of waste generated during the production process is currently suboptimal, as it is immediately disposed of into the environment. This improper waste management poses a threat to both human well-being and the natural ecosystem. The right to a clean and healthy environment is guaranteed by Article 28H, paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The activities conducted aim to empower women farmer groups to effectively manage the waste produced during their production activities, thereby contributing to sustainable development. Through waste and packaging materials awareness campaigns, the women farmer groups have shown enthusiasm for adopting environmentally-friendly production practices.